Faster, better, stronger : 10 proven secrets to a healthier body in 12 weeks - Heiden, Eric.; Testa, Massimo; Musolf, DeAnne (New York, NY : Collins Living, 2008)
A five-time Olympic gold medalist and a U.S. Olympic team physician present a fitness program based on a philosophy of applying exercise as a prescription medication, in a guide that discusses key principles in fitness and weight loss.
Includes bibliographical references (p. [287]-297) and index.
Keywords: Physical fitness